Novel Energy Efficient Protocols with Realistic Radio Propagation Models for Wireless Sensor Networks in Agriculture - Latifah Munirah Kamarudin (School of Computer and Communication Engineering, 2012)
This thesis focuses on the simulation of the proposed novel energy e_cient protocols that are robust to variations in the radio propagation environment. The proposed protocols ensure the connectivity between the cluster members and cluster head (CH), applicable for dense networks, low network overhead and most importantly, energy efficient.